2002
DOI: 10.1177/1099636202004001037
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and Curvature Effects on the Damage Tolerance of Impacted Composite Sandwich Panels

Abstract: An experimental program was conducted to investigate the effects of specimen width and specimen curvature on the residual compression strength of composite sandwich panels after low-energy impact. Flat and curved (1.1 m radius) specimens of three widths (83, 152, and 305 mm) were manufactured from thin-gage (four plies) graphite/epoxy facesheets and 25.4-mm-thick Nomex core. A drop mechanism was used to create barely visible impact damage on one facesheet of the panels (convex face of the curved panels) mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…While along the longitudinal direction (y-axis), indentation propagation is arrested at locations near the edges of initially crushed core after the stroke ΔD exceeds 0.1 mm. These indentation propagation behaviors are exactly the same as what were observed in the SCAI tests [8] . In general, the deformation profile along x-axis is in the shape of a 'W' with a small bubble in the middle of residual indentation, while the one along y-axis is in a shape of letter 'V'.…”
Section: Indentation Propagationsupporting
confidence: 81%
See 3 more Smart Citations
“…While along the longitudinal direction (y-axis), indentation propagation is arrested at locations near the edges of initially crushed core after the stroke ΔD exceeds 0.1 mm. These indentation propagation behaviors are exactly the same as what were observed in the SCAI tests [8] . In general, the deformation profile along x-axis is in the shape of a 'W' with a small bubble in the middle of residual indentation, while the one along y-axis is in a shape of letter 'V'.…”
Section: Indentation Propagationsupporting
confidence: 81%
“…SCAI tests conducted at the Composite Research Laboratory (CORE) at University of Maryland at College Park successfully revealed the damage propagation behavior of low-velocity impacted composite sandwich panels under in-plane uniaxial compression [8] . Sandwich panels, comprising of two thin laminated facesheets and honeycomb core, were manufactured with dimensions of 356 mm in length, 82 mm in width, and 25.6 mm in thickness.…”
Section: Sandwich Compression After Impact Testmentioning
confidence: 97%
See 2 more Smart Citations
“…A number of new studies appeared later, e.g. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], but mainly dealing with experimental and finite-element (FE) results; only [11,15] present analytical failure models.…”
Section: Introductionmentioning
confidence: 99%